First demonstration of on-chip interpolation using a single photon counting microstrip detector. (1st November 2022) - Bergamaschi, A.; Andrä, M.; Barten, R.; Baruffaldi, F.; Brückner, M.; Carulla, M.; Chiriotti, S.; Dinapoli, R.; Fröjdh, E.; Greiffenberg, D.; Hasanaj, S.; Heymes, J.; et al.
Abstract: Despite being used in many X-ray applications, hybrid single photon counting detectors are limited in spatial resolution due to the diffusion of the charge produced by single photons between neighboring electronic channels, also called charge sharing. In this work, we demonstrate that on-chip interpolation can be used to improve the effective spatial resolution in a single photon counting detector without increasing the number and density of interconnects between the sensor and the readout electronics. We describe a digital communication scheme between neighboring channels exploiting charge sharing to obtain a spatial resolution better than the channel pitch, which has been implemented for the first time in the MYTHEN III microstrip detector. The interpolation is achieved directly on-chip at the time the photons are absorbed, limiting the data throughput and the computational effort and allowing a higher photon flux compared to interpolation using analog detectors. Here we show the first results obtained with this interpolation mechanism, characterizing the spatial resolution in terms of modulation transfer function. The spatial resolution of the 50 μm pitch MYTHEN III microstrip detector can be improved from the 20 lp/mm given by the physical strip pitch to an average resolution of approximately 30 lp/mm using the interpolation method.